Analizy semantyczne groźby jako aktu mowy. Ujęcie przeglądowo-krytyczne - Falana-Jafra, Anna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The aim of the article is to present an overview of the semantic analyses of threat understood as a speech act that have been so far conducted in Polish linguistic studies. The overview includes three selected analyses. The first one is based on the idea of necessary and sufficient conditions proposed by Anna Wierzbicka. The second is Joanna Wołoszyn’s work based on a methodology developed in line with structural semantics and attempts to define the terms straszyć (to scare) and grozić (to threaten). The third one is an analysis by Roman Kalisz and Wojciech Kubiński based on prototypical effects in speech acts, meaning that it relies on the methodology of cognitive linguistics. The overview is complemented by a critical analysis focused on identifying the imperfections of all three ideas presented in it and by a presentation of possible and legitimate improvements.